Chronic helminth infection does not exacerbate Mycobacterium tuberculosis infection. - Marc P Hübner; Kristin E Killoran; Michael Rajnik; Samuel Wilson; Kevin C Yim; Marina N Torrero; Christopher P Morris; Boris Nikonenko; Jorge C G Blanco; Val G Hemming; Edward Mitre (Public Library of Science (PLoS), 2012)
Chronic helminth infections induce a Th2 immune shift and establish an immunoregulatory milieu. As both of these responses can suppress Th1 immunity, which is necessary for control of Mycobacterium tuberculosis (MTB) infection, we hypothesized that chronic helminth infections may exacerbate the course of MTB.Co-infection studies were conducted in cotton rats as they are the natural host for the filarial nematode Litomosoides sigmodontis and are an excellent model for human MTB. Immunogical responses, histological studies, and quantitative mycobacterial cultures were assessed two months after MTB challenge in cotton rats with and without chronic L. sigmodontis infection. Spleen cell proliferation and interferon gamma production in response to purified protein derivative were similar between co-infected and MTB-only infected animals. In contrast to our hypothesis, MTB loads and occurrence and size of lung granulomas were not increased in co-infected animals.These findings suggest that chronic filaria infections do not exacerbate MTB infection in the cotton rat model. While these results suggest that filaria eradication programs may not facilitate MTB control, they indicate that it may be possible to develop worm-derived therapies for autoimmune diseases that do not substantially increase the risk for infections.